HOXA4 Gene Promoter Hypermethylation as an Epigenetic Mechanism Mediating Resistance to Imatinib Mesylate in Chronic Myeloid Leukemia Patients. (26th December 2012) - Elias, Marjanu Hikmah; Baba, Abdul Aziz; Husin, Azlan; Sulong, Sarina; Hassan, Rosline; Sim, Goh Ai; Abdul Wahid, S. Fadilah; Ankathil, Ravindran
Abstract : Development of resistance to imatinib mesylate (IM) in chronic myeloid leukemia (CML) patients has emerged as a significant clinical problem. The observation that increased epigenetic silencing of potential tumor suppressor genes correlates with disease progression in some CML patients treated with IM suggests a relationship between epigenetic silencing and resistance development. We hypothesize that promoter hypermethylation of HOXA4 could be an epigenetic mechanism mediating IM resistance in CML patients. Thus a study was undertaken to investigate the promoter hypermethylation status of HOXA4 in CML patients on IM treatment and to determine its role in mediating resistance to IM. Genomic DNA was extracted from peripheral blood samples of 95 CML patients (38 good responders and 57 resistant) and 12 normal controls. All samples were bisulfite treated and analysed by methylation-specific high-resolution melt analysis. Compared to the good responders, the HOXA4 hypermethylation level was significantly higher (P = 0.002 ) in IM-resistant CML patients. On comparing the risk, HOXA4 hypermethylation was associated with a higher risk for IM resistance (OR 4.658; 95% CI, 1.673–12.971; P = 0.003 ). Thus, it is reasonable to suggest that promoter hypermethylation of HOXA4 gene could be an epigenetic mechanism mediating IM resistance in CML patients.